Cambios nictemerales de variables físicas y químicas en la Ciénaga de Paticos, complejo cenagoso de Ayapel, Colombia (2009)
ABSTRACT: The nictemeral variation of abiotic factors in a key factor for tropical organisms. We evalu- ated some climatic, physical and chemical variables during four surveys of the hydrologic cycle in the Paticos wetland (8o21’08.2” N, 75o08’45.7” W). Of climatic variables, pluviosity presented the highest variation (C.V. = 1 022 %) followed by air temperature (C.V. = 19.7%). There was a high relation in the coefficients of variation for these variables (84:1). This relation may be associated with altitude. Throughout the day-night cycle, most variables presented significant differences; except for pluviosity, air and water temperature (because of their high variability). Variables most related with nictemeral variation were pluviosity, wind speed and direction, air temperature and dissolved oxygen.